Optimizing Financial Performance: A Comprehensive Analysis of PT Astra Agro Lestari Tbk's Liquidity and Solvency - Kusnanto, Danang; Rahman, Zaidan Al; Alam, Muhammad Nur; Nugraha, Nugraha (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2024)
This research examines the financial performance of PT Astra Agro Lestari Tbk, one of Indonesia's largest palm oil producers, during the period of 2018-2022. The primary focus of the study is the analysis of liquidity and solvency ratios, aiming to provide an in-depth understanding of the challenges and opportunities faced by the company in the dynamics of the global market. The research adopts a quantitative descriptive approach, utilizing data from the company's public financial reports. The analysis results reveal fluctuations in the liquidity and solvency of the company. Despite facing challenges in 2019, the company managed to improve its performance. However, it was observed that the company exhibits a high dependency on long-term debt. As a recommendation, this research suggests that the company should formulate a more balanced financial policy to reduce risks and enhance flexibility amid economic uncertainties. These measures are expected to assist the company in navigating market dynamics more effectively and ensuring optimal financial sustainability.